Parent‐of‐origin effects on carcass traits in Japanese Black cattle. (19th February 2019) - Okamoto, Kan; Oishi, Kazato; Nakamura, Ryoichi; Abe, Atsuko; Inoue, Keiichi; Kumagai, Hajime; Hirooka, Hiroyuki
Abstract: Variances caused by the differential expression of paternally and maternally imprinted genes controlling carcass traits in Japanese Black cattle were estimated in this study. Data on marbling score (BMS), carcass weight, rib thickness, rib‐eye area (REA) and subcutaneous fat thickness (SFT) were collected from a total of 13, 115 feedlot steers and heifers in a commercial population. A sire–maternal grandsire model was used to analyse the data, and then, imprinting parameters were derived by replacing the genetic effect of the dam with the effect of the maternal grandsire in the imprinting model to calculate the genetic parameter estimates. The proportions of the total genetic variance attributable to imprinted genes ranged from 8.7% (SFT) to 35.2% (BMS). The remarkably large imprinting variance of BMS was mainly contributed by maternally expressed inheritance because the maternal contribution of the trait was much larger than that of the paternal trait. The parent‐of‐origin effect originating from maternal gene expression was also observed for REA. The results suggested the existence of genomic imprinting effects on the traits of the Japanese Black cattle. Hence, the parent‐of‐origin effect should be considered for the genetic evaluation of Japanese Black cattle in breeding programmes.